A decade of treating traumatic sternal fractures in a single-center experience in Korea: a retrospective cohort study - Na Hyeon Lee; Seon Hee Kim; Jae Hun Kim; Ho Hyun Kim; Sang Bong Lee; Chan Ik Park; Gil Hwan Kim; Dong Yeon Ryu; Sun Hyun Kim (Journal of Trauma and Injury)
Purpose Clinical reports on treatment outcomes of sternal fractures are lacking. This study details the clinical features, treatment approaches, and outcomes related to traumatic sternal fractures over a 10-year period at a single institution. Methods A retrospective cohort study was conducted of patients admitted to a regional trauma center between January 2012 and December 2021. Among 7,918 patients with chest injuries, 266 were diagnosed with traumatic sternal fractures. Patient data were collected, including demographics, injury mechanisms, severity, associated injuries, sternal fracture characteristics, hospital stay duration, mortality, respiratory complications, and surgical details. Surgical indications encompassed emergency cases involving intrathoracic injuries, unstable fractures, severe dislocations, flail chest, malunion, and persistent high-grade pain. Results Of 266 patients with traumatic sternal fractures, 260 were included; 98 underwent surgical treatment for sternal fractures, while 162 were managed conservatively. Surgical indications ranged from intrathoracic organ or blood vessel injuries necessitating thoracotomy to unstable fractures with severe dislocations. Factors influencing surgical treatment included flail motion and rib fracture. The median length of intensive care unit stay was 5.4 days (interquartile range [IQR], 1.5–18.0 days) for the nonsurgery group and 8.6 days (IQR, 3.3–23.6 days) for the surgery group. The median length of hospital stay was 20.9 days (IQR, 9.3–48.3 days) for the nonsurgery group and 27.5 days (IQR, 17.0 to 58.0 days) for the surgery group. The between-group differences were not statistically significant. Surgical interventions were successful, with stable bone union and minimal complications. Flail motion in the presence of rib fracture was a crucial consideration for surgical intervention. Conclusions Surgical treatment recommendations for sternal fractures vary based on flail chest presence, displacement degree, and rib fracture. Surgery is recommended for patients with offset-type sternal fractures with rib and segmental sternal fractures. Surgical intervention led to stable bone union and minimal complications.